Actinide Pnictinidene Chemistry: A Terminal Thorium Parent‐Arsinidene Complex Stabilised by a Super‐Bulky Triamidoamine Ligand. (16th November 2022) - Du, Jingzhen; Balázs, Gábor; Seed, John A.; Cryer, Jonathan D.; Wooles, Ashley J.; Scheer, Manfred; Liddle, Stephen T.
Abstract: We report the direct synthesis of the terminal pnictidenes [An(Tren TCHS )(PnH)][M(2, 2, 2‐cryptand)] (Tren TCHS ={N(CH2 CH2 NSiCy3 )3 } 3− ; An/Pn/M=Th/P/Na 5, Th/As/K 6, U/P/Na 7, U/As/K 8 ) and their conversion to the pnictides [An(Tren TCHS )(PnH2 )] (An/Pn=Th/P 9, Th/As 10, U/P 11, U/As 12 ). Use of the super‐bulky Tren TCHS ligand was essential to accessing complete families, and 6 is an unprecedented example of a terminal thorium‐arsinidene complex and only the second structurally authenticated parent terminal arsinidene complex of any metal. Comparison of the terminal Th=AsH unit of 6 to the bridging ThAs(H)K linkage in structurally analogous [Th(Tren TIPS ){μ‐As(H)K(15‐crown‐5)}] (Tren TIPS ={N(CH2 CH2 NSiPr i 3 )3 } 3− ) reveals a stronger Th−As bond in the former compared to the latter, and a large response overall to the nature of the Th=AsH bonding upon removal of the electrostatically‐bound K‐ion; the σ‐bond changes little but the π‐bond is significantly perturbed. Abstract : Introducing a new super‐bulky triamidoamine ligand to actinide chemistry has enabled the previously elusive terminal parent thorium‐arsinidene linkage, that is the first terminal thorium‐arsinidene, to be synthesised and isolated. Quantum chemical calculations reveal a surprisingly large change to the Th=AsH linkage compared to an electrostatically‐bound potassium‐capped analogue.